Case Report: Comorbid Hyper-IgD Syndrome and Hidradenitis Suppurativa – A New Syndromic Form of HS? A Report of Two Cases - Guillem, Philippe; Mintoff, Dillon; Kabbani, Mariam; Cogan, Elie; Vlaeminck-Guillem, Virginie; Duquesne, Agnes; Benhadou, Farida (Frontiers in Immunology, 2022)
Hidradenitis Suppurativa (HS) is a chronic suppurative disease of the pilosebaceous unit. The current model of HS pathophysiology describes the condition as the product of hyperkeratinization and inflammation at the hair follicular unit. Environmental factors (such as smoking and obesity), gender, genetic predisposition, and skin dysbiosis are considered the main pathogenic drivers of the disease. Autoinflammatory syndromes associated with HS are rare but may help to highlight the potential roles of autoinflammation and dysregulated innate immune system in HS. Therefore, it is of major relevance to increase the awareness about these diseases in order to improve the understanding of the disease and to optimize the management of the patients. Herein, we report for the first time, to our knowledge, two clinical cases of Hyper-IgD syndrome-associated HS. Hyper-IgD is an autoinflammatory syndrome caused by a mevalonate kinase deficiency (MKD), a key kinase in the sterol and isoprenoid production pathway. We describe the potentially shared pathophysiological mechanisms underpinning comorbid MKD-HS and propose therapeutic options for the management of these patients.